An interdisciplinary approach to the management of a young patient with generalized periodontitis - A case report with a 3-year follow-up - Gulnar Dara Sethna; Ameya Gajanan Moghe; Sapna Poshanna Sonkurla; Avinash Mahadev Kamble; Anita Kapri; Shobha Rajanna (Wolters Kluwer Medknow Publications, 2020)
Periodontitis has a multifactorial etiology as a result of interactions between periodontal pathogens and the host response. Due to the complex etiology and esthetic complications, the management of such patients is a challenging task. Vast arrays of treatment modalities are employed in the treatment of generalized periodontitis with varying success rates. Placental-derived tissues as allografts have recently been introduced for guided tissue regeneration in dentistry with favorable results. In this case report, successful periodontal treatment of a 25-year-old male patient with generalized periodontitis; Stage IV, Grade C, is presented with a 3-year follow-up. An interdisciplinary approach using regenerative periodontal surgery and a modified Andrew's bridge was used to successfully rehabilitate the patient. In a compliant patient with a well-structured interdisciplinary approach, questionable and hopeless teeth too can be retained over an extended period of time with no detrimental effect on the adjacent teeth.